Effect of Exercise on Sternoceleidomastoid Muscular Fibrosis after Radiotherapy for Nasopharyngeal Carcinoma Patients Analyzed by Shear-Wave Elastography - HE Cui; YI Wenhong; LUO Baolong; WEN Yuanyuan; CAO Junyan; GUO Libing (康复学报)
ObjectiveTo evaluate the therapeutic effect of rehabilitation on sternoceleidomastoid muscular fibrosis after radiotherapy (RT) for nasopharyngeal carcinoma (NPC) patients by shear-wave elastography, and to provide a new clinical approach to solve radiation-induced muscular fibrosis.MethodsA total of twenty NPC patients who had received radiotherapy for 1.5-5 years and rehabilitation therapy for three months were enrolled. Cervical spine range of movement (ROM), the thicknesses, widths and Young's module values of sternoceleidomastoid muscles were assessed before and after treatment.ResultsThe thickness of right and left sternoceleidomastoid muscles was significant different before and after treatment (P<0.05). The widths of right and left sternoceleidomastoid muscles were significant different before and after treatment (P<0.05). Compared with those before treatment, the Young's module values of right and left sternoceleidomastoid muscles were significant different after treatment (P<0.05). The left and right rotations and right flexion ROM of cervical spine were significant different before and after treatment (P<0.05), while the left flexion, anteflexion and extension ROM of cervical spine were not significant different (P>0.05).ConclusionThe Young's module values of sternoceleidomastoid muscles for NPC patients decreased after rehabilitation, while the cervical spine ROM of left and right rotations and right flexion, as well as widths and thickness of sternoceleidomastoid muscles increased after rehabilitation. The shear-wave elastography is a feasible way to evaluate the effectiveness of radiation-induced muscular fibrosis rehabilitation for NPC patients.